1990
DOI: 10.1111/j.1475-097x.1990.tb00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Coronary circulation in acute hypoxia

Abstract: Healthy young men were subjected to different degrees of hypoxia at rest and during increased levels of cardiac work induced by atrial pacing and physical exercise at submaximal and maximal loads. Coronary sinus (cs) blood flow was measured by thermodilution and a-cs differences of O2 and lactate were obtained. At low cardiac power output (rest, pacing) the reduction in arterial oxygen content was compensated for mainly by a more complete myocardial oxygen extraction producing lowered cs O2 saturation and tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 7 publications
(4 reference statements)
3
16
0
Order By: Relevance
“…In controls, exercise-induced hyperemia at altitude was significantly increased by 38% (PϽ0.01) compared with normoxia, although target RPP was reached at a significantly lower workload level (Ϫ28%, PϽ0.0001), probably due to hypoxia-induced sympathetic activation, which might also increase myocardial contractility. This is in agreement with previous invasive measurements by Kaijser and coworkers,18 who found that during physical exercise, the hypoxia-induced reduction in O 2 content was compensated for mainly by an increase in MBF of 33%. So far, no data are available for patients with CAD.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In controls, exercise-induced hyperemia at altitude was significantly increased by 38% (PϽ0.01) compared with normoxia, although target RPP was reached at a significantly lower workload level (Ϫ28%, PϽ0.0001), probably due to hypoxia-induced sympathetic activation, which might also increase myocardial contractility. This is in agreement with previous invasive measurements by Kaijser and coworkers,18 who found that during physical exercise, the hypoxia-induced reduction in O 2 content was compensated for mainly by an increase in MBF of 33%. So far, no data are available for patients with CAD.…”
Section: Discussionsupporting
confidence: 93%
“…28 However, only very few reports in the literature deal with the use of physical exercise in PET, 29 -31 and only recently has its reproducibility been documented. 18 In the present study, exercise-induced, hyperemic flow was higher in patients than in controls, possibly indicating an uncoupling of MBF and cardiac work due to inefficient contractility of the ischemic heart. In fact, as patients had a significantly decreased maximal adenosine-induced MBF, they utilized Ϸ90% of their available maximal MBF during physical exercise.…”
Section: Discussionsupporting
confidence: 41%
“…However, this mechanism is protective for the heart, a vital organ that is also demanding for a high O 2 supply at exercise. The coronary fl ow reserve has been shown to be limited to 33 % above what is prevailing during maximal exercise at sea level [ 20 ]. Therefore, the compensation of decreased arterial O 2 content by increasing coronary blood fl ow is not possible above a certain altitude and the only option to preserve cardiac integrity is to decrease myocardial O 2 demand and therefore maximal heart rate.…”
Section: Adrenergic System and Preservation Of The Myocardium In Hypoxiamentioning
confidence: 99%
“…Kaijser et al, 18 our results show that there are no significant changes in MBF in healthy human beings at a moderate altitude of 2000 m. This may explain the fact that even patients with CAD and impaired left ventricular function tolerate these conditions well, 25 because no sizeable flow reserve seems to be required to meet the myocardial oxygen demand during the slight decrease in PO 2 at 2000 m. However, at high altitudes such as 4500 m, an increase in MBF of 62% is observed despite the concomitant decrease in PEtCO 2 . A hypoxia-induced increase in heart rate due to sympathetic activation and vagal withdrawal could increase myocardial oxygen consumption because of an increase in cardiac work 26 and thus could also account for increased MBF.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, MBF is regulated to maintain constant myocardial tissue oxygen tension. 17 However, Kaijser et al 18 found an enhanced oxygen extraction at rest during acute exposure to an altitude of 2300 m and no change in MBF, which increased during physical exercise. Thus it remains unclear whether a reduced coronary vasodilator capacity (such as that in patients with CAD) represents a risk factor during acute exposure to hypoxia.…”
mentioning
confidence: 99%